2011
DOI: 10.1021/jp208384b
|View full text |Cite
|
Sign up to set email alerts
|

Control of 1,3-Cyclohexadiene Photoisomerization Using Light-Induced Conical Intersections

Abstract: We have studied the photoinduced isomerization from 1,3-cyclohexadiene to 1,3,5-hexatriene in the presence of an intense ultrafast laser pulse. We find that the laser field maximally suppresses isomerization if it is both polarized parallel to the excitation dipole and present 50 fs after the initial photoabsorption, at the time when the system is expected to be in the vicinity of a conical intersection that mediates this structural transition. A modified ab initio multiple spawning (AIMS) method shows that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
113
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 60 publications
2
113
0
Order By: Relevance
“…Because of the presence of several vibrational degrees of freedom, LICIs exist also without rotations and become multidimensional in nuclear coordinate space [12]. This opens the door for manipulating and controlling nonadiabatic effects by light [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the presence of several vibrational degrees of freedom, LICIs exist also without rotations and become multidimensional in nuclear coordinate space [12]. This opens the door for manipulating and controlling nonadiabatic effects by light [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The non-adiabatic effects emerging from LICIs should be amenable to control because of possibility to shape the properties of the LICI by laser frequency, duration, intensity, and polarization. The concept of LICIs can also be applied to polyatomic molecules, as shown in a recent laser-induced isomerization experiment [25]. The main difference here compared to the case of diatomic molecules is that several internal nuclear degrees of freedom may be relevant for the formation of the LICI.…”
mentioning
confidence: 99%
“…However, recent experiments have shown that it is possible to achieve unprecedented control over photodissociation reactions. [8][9][10] . The LIPs provide a new playground where essentially new electronic states are created and these new chemical species are an open door to control the chemistry of simple molecules or to increase our understanding of the molecular dynamics in excited states.…”
Section: Discussionmentioning
confidence: 99%
“…[109] Although most proposals remain experimentally untested, owing to the difficulty of finding good molecular systems where the strong field interaction is strong enough to generate LIPs, yet not too strong that the ionization is predominant, recent experiments have shown that indeed such control is possible. [8][9][10] In this work, we will review some of our findings. In LightInduced Potentials: Geometrical and Dynamical Features Section, we will provide a simplified analysis of the geometrical and dynamical features of LIPs, outlining the role of the Starkshift and of laser-induced potential energy shaping in several control scenarios.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation